Design and in vitro Evaluation of Fluvoxamine Nanosuspension using PVA as Stabilizing Agent - Srinivas, Martha (Asian Journal of Pharmaceutics (AJP), 2021)
Introduction: Poor aqueous solubility and low dissolution rates are the initial drawback for the majority of upcoming and existing biologically active compounds. Materials and Methods: Fluvoxamine (API), other excipients such as PVA, SLS, Tween 80, and methanol. Fluvoxamine is a poorly water-soluble drug and its bioavailability is very low. The present study was to increase the solubility and dissolution rate of Fluvoxamine by formulating nanosuspensions by Emulsification solvent evaporation method. Results and Discussions: The formulation nanosuspenison was subject to zeta potential, particle size analysis, drug content, and in vitro drug release studies. The entrapment efficiency of all the formulations was within 95.78–98.16%, from the drug release studies, The NF6 formulation was optimized and it shows maximum drug release (99.02%) at a shorter period of time than remaining formulations. The average particle size of the optimized formulation was found to be 110 nm. Conclusion: The research showed that enhanced dissolution rate by reduced in particle size, which, in turn, increases the dissolution rate and oral bioavailability of fluvoxamine by formulating nanosuspensions. Formulations were found to physically stable with PVA as the stabilizing agent.